Bismuth Sulfide Strongly Coupled to Functionalized MWNTs Hybrids with Improved Thermoelectric Properties. (26th July 2021) - Liao, Yu; Liu, Wenting; Jia, Weiping; Wang, Bo; Chen, Ling; Huang, Ke; Montgomery, Matthew J.; Qian, Jun; Lv, Song; Pfefferle, Lisa D.
Abstract: The efficiency of thermoelectric (TE) materials depends on an interplay between various material properties, and strategies for co‐optimizing these properties will be necessary for implementing these materials in the future. In this work, bismuth sulfide (Bi2 S3 ) and acid treated multiwalled carbon nanotube (f‐MWNT) composites are fabricated by wet chemical synthesis at room temperature. Bi2 S3 is intimately anchored onto the surface of the f‐MWNT to form a coaxial nanostructure. The power factor of the composite is enhanced relative to both the pure Bi2 S3 and MWNTs, due to a large enhancement of the electrical conductivity. The enhanced conductivity is attributed to restructuring of the bismuth (Bi) and oxygen (O) bonding environments when Bi2 S3 is chemically interfaced with the f‐MWNTs, suggestive of the formation of a strongly coupled complex via BiO/BiS bonds. Strong‐coupling is further supported by scanning transmission electron microscopy, Raman, and diffuse reflectance spectroscopy, which reveal fast charge‐transfer between the Bi2 S3 and MWNT when interfaced together. These results support material compositing as a potential strategy for engineering enhanced TE materials. Abstract : Bismuth sulfide (Bi2 S3 ) and f‐MWNT composites are fabricated by wet chemical synthesis at room temperature. Bi2 S3 is intimately anchored onto the surface of the f‐MWNT to form a coaxial nanostructure. The power factor of the composite is enhanced relative to both the pure Bi2 S3 and MWNTs, due to a large enhancement of the electrical conductivity.